Evaluation of taro (Colocasia esculenta)-based cropping system for crop diversification under rainfed upland ecosystem of eastern India (Current Horticulture, 2024)
A field experiment was conducted at the Regional Centre of ICAR-Central Tuber Crops Research Institute, Bhubaneswar, Odisha,  India, during 2018-2020 on alfisols under rainfed conditions to identify most productive, resource use-efficient and remunerative  taro-based cropping system. The experiment consisted of seven treatments, T1- sole taro, T2- sole maize, T3- sole pigeonpea, T4-  taro+maize (5:1), T5- taro+maize (5:2), T6- taro+pigeonpea (5:1) and T7- taro+pigeonpea (5:2). The results revealed that the cormel  equivalent yield (CEY) was greater in T1 and it was statistically on a par with T4 and T6. The LER of T4, T5, T6 and T7 were found >1.  This indicated that all the above intercropping systems were biologically efficient. However, advantage of intercropping system was  disappeared in T5, T6 and T7, when evaluated via ATER concept. The treatment T1 resulted in higher gross and net returns as well as  B:C ratio however, it was statistically on a par with T4 and T6. Taro can be recommended for cultivation as a sole crop under upland  ecosystem of eastern India. The treatment taro+maize (5:1) (T4) can also be recommended for cultivation under rainfed conditions  of eastern India for efficient use of resources, and optimum yield and returns. The intercropping system taro+pigeonpea (5:1) (T6) can  also be considered when more emphasis was given on soil health.
Keywords: Area time equivalent ratio; Cormel equivalent yield; Gross and net returns; Land equivalent ratio